Intraspecific identification of Actinidia eriantha Benth. based on chloroplast genes - Lan Lan; Jiale Mao; Bingyan Mao; Shuang Liu; Tao Li; Xiaohui Zhou; Houxing Lei; Songquan Wu; Jia Chen; Xiaoqin Zhang (PLoS ONE, 2026)
Objective This study aimed to identify specific DNA barcodes based on the chloroplast genome of Actinidia eriantha Benth. and to utilize these barcodes for the identification of germplasm resources from different geographic origins. Methods The chloroplast genome of A. eriantha samples were sequenced using the Illumina NovaSeq PE150 platform. Specific highly variable regions were identified through mVISTA alignment and nucleotide diversity analysis. Haplotypes of samples from various regions were further analyzed based on the selected DNA barcode candidate fragments. Results The complete chloroplast genomes of three A. eriantha from different locations were 156,955–157,100 bp in length and exhibited a typical quadripartite circular structure, with 88 genes annotated in each genome. Comparative analyses with mVISTA and nucleotide diversity indices identified matK , trnK(UUU) , ycf1 , and the atpH_atpI intergenic spacer as candidate regions for specific DNA barcodes. Among these, trnK(UUU) , ycf1 , and atpH_atpI were selected for further analysis based on PCR amplification efficiency. Sequencing of these three regions across 223 samples from 21 locations in six provinces revealed 7, 10, and 39 polymorphic sites, respectively, which defined 6, 4, and 6 haplotypes. A combined analysis of the three loci identified 56 polymorphic sites and 12 distinct haplotypes (Hap1-Hap12), with pairwise genetic distances ranging from 0 to 1.96%. Six haplotypes were found to be unique to specific geographic regions, suggesting their potential as molecular markers for tracing the geographic origin of A. eriantha . Conclusion The chloroplast gene regions trnK(UUU) , ycf1 , and atpH_atpI , identified through comparative chloroplast genomics, serve as effective DNA barcodes for the intraspecific identification of A. eriantha germplasm. These markers provide a molecular basis for future efforts in geographic origin tracing, germplasm conservation, and breeding of this species.